Perspective: Daniela Novick, cytokines and their receptors - Ghezzi, Pietro; Fantuzzi, Giamila; Dinarello, Charles A. (Frontiers in Immunology, 2023)
This Perspective highlights the work of Dr. Daniela Novick in the field of cytokine biology. Using affinity chromatography to characterize cytokine-binding proteins, she identified soluble forms of the receptors as well as binding proteins for several cytokines, including tumor necrosis factor, interleukin (IL) 6, IL-18 and IL-32. Importantly, her work has been key in the development of monoclonal antibodies against interferons and cytokines. This Perspective discusses her contribution to the field and highlights her recent review on this topic.